Children's ability to coordinate perspectives of isolated objects implications for science curriculum development - Licup, Nora Librado- 1949- (1978)
This study was an effort to determine the quality or stage of children's thinking regarding a space-related concept, perspective or how an object looks from different positions such as the front, side, back, or top view. Knowing children's perspective abilities can provide a useful basis for planning more appropriate elementary science activities. The subjects were 60 children from Tambo Elementary School, a typical rural school in the town of Buhi, and 60 children from Elementary Department of the University of Nueva Caceres, a typical urban school in Naga City. Within the limitations of the study, the results cannot be very conclusive. However, the tentative findings can provide a fairly strong rationale for providing children with experiences that develop spatial abilities, including perspective, through the elementary science curriculum.
Vita.
Thesis [M.A.T. : Elementary Science]--University of the Philippines, Diliman.
Keywords: Space perception in children -- Philippines -- Naga City (Camarines Sur).